Writing the complete truth by Filip Topol. Authenticity as textuality - Dokulilova, Kristina (Bohemica Olomucensia, 2020)
Filip Topol himself has often confessed to a strong aura of authenticity which was created around his personality from the very beginning. I would like to uncover this phenomenon in his prosaic debut. In the introduction I try to resist the concept of authenticity in the sense of true representation of reality in his work. I perceive authenticity as the author's intention, which he inscribes in the text during writing process. Authenticity is thus inscribed in the text by the author as an instruction intended to trigger this effect on the reader. Therefore we will focus on certain textual features, which have an authentic effect on the perceiver. This is not only caused by a mere isolated enumeration but mainly by their specific correlation in the text. These language elements that we recognize in the text as ``authentic'' are features with a pragmatic dimension, which means that they require anchoring in a particular context, be it a link to the text, the author's life, or a general social context which is introduced by literary underground.
Keywords: authenticity; authentic effect; text construction; pragmatic dimension of features; role of context